Consumers’ Decision-Making Process on Social Commerce Platforms: Online Trust, Perceived Risk, and Purchase Intentions - Lăzăroiu, George; Neguriţă, Octav; Grecu, Iulia; Grecu, Gheorghe; Mitran, Paula Cornelia (Frontiers in Psychology, 2020)
This study enhances the existing literature on the role of trust and online perceived risk in shaping consumer purchase decision-making in social commerce. The aim of this article is to investigate consumers’ purchase decision-making process, the determinant components of social commerce purchase intentions and attitudes, the effect of perceived risk on intention to go shopping in online settings, and consumer trust and buying behavior on online retailing platforms. The insights obtained from our research extend current knowledge as regards determinants of consumer attitudes and intentions towards online purchases, consumers’ perceived shopping risk and repurchase behavior when buying products online, and perceived consumer online trust and purchase decisions. Limited research has considered consumers’ decision-making processes on social commerce platforms by investigating how their perceptual attitudes, behavioral intentions, and immediate gratifications affect the purchase of products and services online. Our study addresses this gap and extends prior research by focusing on the relationship between online consumer purchase intention, social commerce adoption behavior, and consumers’ trust together with risk factors affecting online buying decisions, in light of the characteristics of source credibility. Our findings point towards important avenues of research on psychological determinants of consumer engagement in social media, decision mechanisms lying behind evaluation of prices, the types of perceived risk incurred, and online repurchasing behavior and intention on social commerce platforms. Subsequent directions should clarify whether adoption of mobile payment services may shape online consumers’ impulsive buying behavior and decision-making, especially under the influence of online product reviews.